RANCANGAN ALAT MONITORING PERUBAHAN SUHU PADA SHELTER VOR (VHF OMNIDIRECTIONAL RANGE), SHELTER GLIDE PATH DAN SHELTER LOCALIZER BERBASIS SMS GATEWAY DI BANDAR UDARA INTERNASIONAL HANG NADIM BATAM - Ahmad Rizaldy; Feti Fatonah; Bambang Wijaya Putra (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
By looking at the current conditions the author tries to design a tool that can find out the temperature when an alarm occurs in the equipment room over long distances so that it can be immediately known by the technician to then check the location of the equipment. The working principle of this tool is when the temperature sensor detects temperature changes above the specified limit then the sensor will provide input to the Arduino which then Arduino will turn on the buzzer that is in the VOR shelter, Glide Path and Localizer. Then the transmission media can send SMS warning messages to the technician. After that to make sure whether the SMS is correct, the technician can see the alarm indicator on the VOR shelter, Glide Path and Localizer, because there are cameras installed in the VOR shelter, Glide Path and Localizer. So that technicians can immediately find out without having to come to the location of the equipment and can immediately overcome it. With this temperature detection design it is expected that the temperature conditions at VOR shelter, Glide Path and Localizer can be monitored at any time over long distances by the technician without having to come to the equipment location, this means that it will facilitate the technician's work in knowing the condition of the equipment's room temperature and in anticipation of damage to the equipment.